THE EFFECTIVENESS OF BIOSERUM INJECTION ON AGARWOOD RESIN (Aquilariamalaccensis) FORMATION WITH SEVERAL INJECTION HOLE DISTANCES - Mina Marlina; Melya Riniarti; Rahmat Syafe'i (Universitas Lambung Mangkurat, 2018)
Agarwood has so high value that can trigger an excessive agarwood encroachment in nature; it threatened the agarwood availability. Agarwood cultivation was the right solution to overcome the Agarwood insufficiency. Currently, bioserum has been found to form Agarwood rapidly. It was found by Kusnadi and introduced to the public by BPDASHLWSS (The watershed management and protection forest inquiry). The formation and effectiveness process of bioserum has not been researched yet scientifically. Therefore, this study aimed to determine the success rate of Agarwood formation and the quality of Agarwood with combined injections treatments on tree branches of Aquilariamalaccensis. This research used a complete randomized design with 3 treatments. Each treatment consisted of several vertical injection hole spaces: 5 cm, 10 cm, and 15 cm. The horizontal space for these three treatments was the same, 5 cm. The result showed that the best vertical range of injection was 10 cm. Therefore, each injection hole would produce separate agarwood chips. A 10-cm vertical range injection also made the rest wood between the injection holes not too wide. This Agarwood was classified into kamedangan class with the average weight of 2 g/chips.